Knowledge and attitude among Malays in Kuching, Sarawak towards organ donation - Yusmalisa, binti Yaacob (Faculty of Medicine & Health Sciences, 2008)
This study is designed to determine the knowledge and attitude towards organ donation and factors that are prohibiting Malays (the largest race in Malaysia) from registering as organ donor nominator. A descriptive study is conducted to 60 Malay participants for Kuching, Sarawak.